2008
DOI: 10.1007/s10709-008-9247-9
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the male genitalia: morphological variation of the aedeagi in a natural population of Drosophila mediopunctata

Abstract: To investigate the size and shape of the aedeagus of Drosophila mediopunctata, we used basic statistics and geometric morphometrics. We estimated the level of phenotypic variation, natural and laboratory heritability as well as the phenotypic correlations between aedeagus and wing measures. The wing was used as an indicator for both body size and shape. Positive significant correlation was obtained for centroid size of aedeagus and wing for field parents and their offspring reared in the laboratory. Many posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 65 publications
2
16
0
Order By: Relevance
“…It is also consistent with the expected erosion of genetic variation by selection, since E. binotata signals have diverged rapidly under strong sexual selection (Rodríguez et al , 2006Cocroft et al 2010;Sullivan-Beckers and Cocroft 2010). Medium-tohigh H 2 in genitalia is in line with other studies (Arnqvist and Thornhill 1998;Zeng et al 2000;Andrade et al 2009;Higgins et al 2009;Kamimura and Iwase 2010). We detected G 9 E in all signal and body traits and all but one genitalia trait.…”
Section: Discussionsupporting
confidence: 92%
“…It is also consistent with the expected erosion of genetic variation by selection, since E. binotata signals have diverged rapidly under strong sexual selection (Rodríguez et al , 2006Cocroft et al 2010;Sullivan-Beckers and Cocroft 2010). Medium-tohigh H 2 in genitalia is in line with other studies (Arnqvist and Thornhill 1998;Zeng et al 2000;Andrade et al 2009;Higgins et al 2009;Kamimura and Iwase 2010). We detected G 9 E in all signal and body traits and all but one genitalia trait.…”
Section: Discussionsupporting
confidence: 92%
“…Whereas coefficients of variation in genital traits of arthropods are usually substantially lower than those of non-genital traits (e.g. Eberhard et al 1998;Hosken et al 2005;Bertin and Fairbairn 2007; but see also Andrade et al 2009), recent mammalian studies indicate that male genital traits often exhibit higher coefficients of variation compared to non-sexual traits measured in the same species (Miller and Burton 2001;Kinahan et al 2007;Tasikas et al 2009;Miller and Nagorsen 2008), though this is not always the case (e.g. see Long and Frank 1968).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the genetic content of the inversions may have accumulated different alleles adapted to different temperatures. Similarly, Andrade et al (2009) showed that different chromosome karyotypes affected not only wing shape, but also male genital (aedeagus) morphology.…”
Section: Introductionmentioning
confidence: 99%